Diversity of Ground-foraging Ants (Hymenoptera: Formicidae) in Bukit Kasang and Lubuk Bonta, Padang Pariaman District, West Sumatra - Meylia Alvareza; Fitra Arya Dwi Nugraha; Irma Leilani; Rijal Satria (Jurnal Biologi Universitas Andalas, 2020)
The Study of ground-foraging ant diversity was conducted in Bukit Kasang and Lubuk Bonta, Padang Pariaman District, West Sumatera from April to December 2019. The pitfall trap was used to collect the ground-foraging ants on the area in seven type of habitats. A total 35 species belonging to 23 genera, 4 subfamilies were collected, with Camponotus (4 spp.), Pheidole (3 spp.), and Leptogenys (3 spp.) being the taxa with the most species. Myrmicinae is subfamily with the highest number of species with 15 species, followed by Formicinae (10 spp.), Ponerinae (8 spp.) and Dolichoderinae (2 spp.).